The Bidirectional Relationship between Meta-Creativity and Academic Performance in University Students - Lourdes Villalustre; Marisol Cueli; Daniel Zarzuelo (MDPI AG, 2024)
Creativity has been studied in relation to academic performance, usually from the perspective of the creative result, with fewer studies focusing on the creative process and the student's awareness of that process, known as meta-creativity. This study aimed to analyze differences in meta-creativity based on academic performance groups (high or low) and determine the predictive power of meta-creativity belonging to the high or low academic performance groups. A total of 172 university students participated. Meta-creativity was assessed using a Meta-Creativity Questionnaire, which evaluated three dimensions (creative motivation, creative leadership, and divergent thinking). Additionally, academic performance was recorded, allowing for the classification of students based on high and low academic performance. The results of the analysis of variance indicated statistically significant differences between students with high and low academic performance in the three dimensions. Discriminant analysis indicated that the dimensions of meta-creativity were able to predict who belonged to the high and low academic performance groups. The model correctly classified 86.6% of the sample. It can be concluded that academic performance is a good indicator of the level of meta-creativity, and, additionally, meta-creativity has a beneficial effect on academic performance. There is a bidirectional relationship between the two variables.